The Impact of Mobile Learning Applications on Students’ Motivation in Learning English in MTS Neg. 3 Konawe Selatan - Ahmad Junandar; Sam Hermansyah; Maulina; Syarif Amin; Andi Rachmawati Syarif (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The integration of mobile learning applications has emerged as a promising strategy to enhance student engagement in English language learning, particularly in resource-limited educational settings in Indonesia. This study aimed to investigate the impact of mobile learning applications on students’ motivation in learning English at MTs Negeri 3 Konawe Selatan, Southeast Sulawesi. Employing a quasi-experimental design, the research involved 56 ninth-grade students from classes IX A, IX B, and IX C. The experimental group (n = 28) utilized mobile-assisted language learning (MALL) applications, while the control group (n = 28) received conventional classroom instruction over an eight-week period. Students’ motivation was measured using a validated questionnaire based on Keller’s ARCS model (Attention, Relevance, Confidence, and Satisfaction) as pre- and post-tests and analyzed with paired and independent sample t-tests. The results revealed a statistically significant increase in overall motivation scores in the experimental group compared to the control group (p < .05). Notable improvements were observed across all ARCS subscales, particularly in attention and satisfaction. Students reported higher engagement through interactive features, gamification, and flexible learning access. These findings indicate that mobile learning applications can effectively boost EFL learners’ motivation in Indonesian junior secondary schools. The study recommends the pedagogical integration of appropriate mobile technologies to support English teaching and learning in similar contexts.